Percutaneous perfusion monitoring for the detection of hemodialysis induced cardiovascular injury. Issue 3 (23rd January 2018) - Penny, Jarrin D.; Grant, Claire; Salerno, Fabio; Brumfield, Anne; Mianulli, Marcus; Poole, Lori; Mcintyre, Christopher W.
Abstract: Introduction: The safe delivery of hemodialysis (HD) faces dual challenges; the accurate detection of systemic circulatory stress producing cardiovascular (CV) injury, and the ability to enable effective preemptive intervention for such injury. We performed a pilot study to examine the capability of a new noninvasive, real‐time monitoring system to detect the deleterious effects of HD on CV stability. Methods: Eight patients were evaluated with echocardiography prior to the initiation of HD and again at peak HD stress. Continuous CV physiologic monitoring was performed throughout using oximeter‐based pulse waveform analysis (CVInsight ® Monitoring System, Intelomed, Inc., Warrendale, PA, USA). Longitudinal strain (LS) values for 12 left ventricular segments were generated using speckle‐tracking software (EchoPac, GE), to assess the presence of HD‐induced regional wall motion abnormalities (RWMA), indicative of myocardial stunning. Findings: A reduction in pulse strength (PS) of ≥40% detected by CVI was associated with the development of RWMA (P = 0.005). This reduction occurred in 6/8 patients, all of whom exhibited myocardial stunning. Two patients had no significant reduction in PS nor evidence of myocardial stunning. In subjects with cardiac stunning, the decrease in PS was evident early during HD, 11.49 ± 10 minutes into HD treatment, prior to the detection of RWMA, which were assessed at peak HD stress, mean 210 ± 16.43 minutes into HD treatment. Discussion: Percutaneous perfusion monitoring, using pulse wave analysis, appears to be useful in identifying circulatory stress during HD and predicting the development of HD‐induced myocardial stunning with a lead time long enough to consider timely intervention.